Exploration of the Interest of MSME Bussines Actors in Applying For Halal Certification - Rofifah, Zazilatul; Novi Puspitasari; Mochamad Sulthoni (Journal of Management Research and Studies, 2024)
The Micro, Small and Medium Enterprises (MSMEs) industry plays an important role in the Indonesian economy. However, many MSMEs do not yet have halal certification, potentially hindering their business growth. This study aims to explore the lack of interest of MSME business actors in applying for halal certification and explore the factors driving MSME business actors to be interested in taking care of halal certification (Case Study on Umkm Actors in Bondowoso District, Bondowoso Regency). This study uses a Qualitative Descriptive method using an analysis tool, namely semi-structured interview techniques to 8 informants with details of 6 MSME business actors in Bondowoso District, Bondowoso Regency, 1 Head of MSMEs and 1 Head of DISKOPERINDAG. The results showed that most MSME business actors have a high interest in applying for halal certification but there are several obstacles that hinder MSME business actors in applying for halal certification. Their main reasons are to increase consumer confidence, expand the market, and increase business competitiveness.